Risk Management in Slickline Fishing Operations: a Delphi Study - Tri Novaldi; Muhammad Asrol (Universitas Islam Balitar, 2022)
Slickline fishing, as a result of undesired event, is economically preferable compared to workover. However, the fact that it does not always end with success but also worsened situation making it a risk management strategy. This research aims to manage the risk during normal slickline to avoid fish and while performing fishing operations using three-round Delphi study to conduct risk identification and to determine countermeasures by asking panel of selected experts. The results revealed that nine risks to be prioritized in Slickline operations to avoid fishing situation and four less prioritized risks to be considered. It has also revealed that 12 risks to be prioritized during fishing operations to avoid ending up in worse situation and five prioritized risks to be considered. The Delphi reached consensus on 12 countermeasures to be prioritized in Slickline operations to avoid fishing situation and 14 important factors for successful fishing operations.